Ethnographies of Maintenance of a New Self - Shoshana, Avihu (Qualitative Sociology Review, 2016)
This article suggests expanding the discussion regarding the association between educational boarding schools, social class, and one’s sense of self, by examining the issue of how subjects who experienced reconstruction of the self continue to maintain this reconstruction as the years go by. This issue is hereby discussed by way of the case study of the Boarding School for Gifted Disadvantaged in Israel. The subjects of study are defined as “ethnic” (Oriental) and, through the boarding school experience, State authorities carried out their intentional assimilation into mainstream culture. Study findings show that, over the years, boarding school graduates steadfastly participate in the school’s annual Remembrance Day ceremony, in memory of the Fallen Soldiers of Israel (and specifically, the boarding school). Remembrance Day ethnographies and social gatherings held at the homes of boarding school graduates a few days before Remembrance Day show how participation in the Remembrance Day ceremony charges the graduates’ sense of self—instilling in them the same structure that characterized their lives when they were students in the boarding school. Moreover, the structure of Remembrance Day itself (signifying the presence of absence) provides a (symbolic and narrative) charge, maintaining the boarding school graduates’ sense of self and their national identifications.